On the Restricted Projective Dimension of Complexes - Li, Liang; Wu, Dejun (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the restricted projective dimension of complexes and give some new characterizations of the restricted projective dimension. In particular, it is shown that the restricted projective dimension can be computed in terms of the so-called restricted projective resolutions. As applications, we get some results on the behavior of the restricted projective dimension under the change of rings.